Amelogenesis imperfecta with gingival calcification: a rare presentation - Sunitha Carnelio; Nirmala Rao (Universidade Estadual de Campinas, 2015)
The purpose of this article is to highlight the rare presence of gingival calcification with Amelogenesis Imperfecta. A case is presented of a 12-year-old girl with a defect of enamel in deciduous as well as permanent dentition with moderate amount of gingival hyperplasia with no positive family history of a similar condition. On the basis of history, clinical and radiographic features a diagnosis of autosomal recessive hypoplastic amelogenesis imperfecta of rough variant was made. Histopathological examination of hyperplastic gingival tissue revealed the presence of calcified bodies. An attempt is made to determine the nature of these calcified bodies by histochemical examination. The relevant literature is reviewed.